Evaluation of run-over of wild animals on BR-153, trecho Guaraí-Tabocão (Research, Society and Development, 2021)
With the increase in population and vehicle traffic, resulting in the loss of their habitat, wild animals are the main victims of roadkill. Although roads provide human mobility, this action has negative impacts on the environment, such as deforestation, modification of natural landscapes, loss of habitat, reduction of individuals and even the extinction of a species. The present work evaluates critical points of running over by wild and domestic animals related to the stretch in the state of Tocantins of the BR-153 in the municipalities of Guaraí-Tabocão and the impacts on local fauna. For this, the field trip was carried out with photographic records, annotations, and GPS location. This work lasted for 7 months, where 39 animals were found to be run over, all of which were identified, according to the class they belong to and of these we recorded 14 mammals (36%), 15 birds (38%), 8 reptiles (21%), 2 amphibians (5%). Analyzing the surroundings, measures were proposed to reduce accidents by wild and domestic animals and how their respective monitoring can be an important environmental management tool on the roads.